PERAN LEMBAGA CATATAN SIPIL TERHADAP PERKAWINAN CAMPURAN BERDASARKAN UNDANG-UNDANG PERKAWINAN - Laurensius Arliman S (STIH Putri Maharaja, 2019)
The legal aspect of civil registration is to obtain as much legal certainty as possible about personal events. Civil registration institutions are government institutions, the state administrative agency in charge, serves to record all family events and has the right, the authority to issue provisions in the field of population and citizenship. As a result of recording and publishing the provision, it has a legal connection with one's civil status or individual law. With the enactment of Law 1 of 1974 concerning Marriage and PP 9 of 1975 as implementing regulations, the public needs for Civil Registry Institutions are increasingly important. Research on this scientific work was a type of normative legal research. Civil records had carried out the tasks carried out by the state well, namely by serving each party who will report the mixed marriages carried out by the parties as well as possible, which is a problem is the lack of public awareness of the importance of the reporting. The implementation of mixed marriages can be carried out if the parties have fulfilled all the requirements determined by the law as contained in Article 60 Paragraph (1) of Law 1 Year 1974. Whereas the Record Institution was only tasked to record the mixed marriage events. Every legal act carried out by any particular person has an impact or effect both for himself and for the other party. No exception in mixed marriages is the legal consequences that arise, both for mixed marriages and for children born from the mixed marriages.